Using Health Impact Assessments to Evaluate Bicycle and Pedestrian Plans. - Wagner, Laura (My University, 2013)
Where we live, work, and play influences health, as well as how we travel to those places. Transportation agencies are responsible for ensuring safe access to travel options, including walking and bicycling, for people of all ages and abilities. For a number of reasons, including chronic disease rates and changing demographics, there is growing interest across the country to better explore the links between health and transportation. New approaches are emerging that can assist transportation agencies during the transportation planning process to make more informed decisions. One such approach involves the use of Health Impact Assessments (HIA), which can improve decision-making and protect and enhance health and health equity. (PBIC)
Keywords: Individualverkehr; Fahrrad; Verkehrsplanung; Fußgänger; Gesundheitsförderung; Evaluation; Wirkungsanalyse